2013
DOI: 10.1371/journal.pone.0069093
|View full text |Cite
|
Sign up to set email alerts
|

Erosive Arthritis and Hepatic Granuloma Formation Induced by Peptidoglycan Polysaccharide in Rats Is Aggravated by Prasugrel Treatment

Abstract: Administration of the thienopyridine P2Y12 receptor antagonist, clopidogrel, increased the erosive arthritis induced by peptidoglycan polysaccharide (PG-PS) in rats or by injection of the arthritogenic K/BxN serum in mice. To determine if the detrimental effects are caused exclusively by clopidogrel, we evaluated prasugrel, a third-generation thienopyridine pro-drug, that contrary to clopidogrel is mostly metabolized into its active metabolite in the intestine. Prasugrel effects were examined on the PG-PS-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Aspirin-induced COX inhibition enhances the generation of anti-inflammatory lipoxins, such as 15-epi-lipoxin, which has protective effects on post-ischemic hyperperfusion and lung injury (46,75). P2Y 12 is also found on other cell types (76), and exerts non-platelet mediated pro-and anti-inflammatory ef-fects on leukocytes (77,78) and mediates leukocyte migration in transplant arteriosclerosis independently of platelet P2Y 12 (79). The effect of aspirin and P2Y 12 inhibitors on leukocyte functions further seems to depend on the pathological condition of the patient or on the disease models as effects observed in healthy volunteers are not always reflected by patient cohorts (80).…”
Section: Effects Of Aspirin and P2y 12 Antagonists On Platelet-leukocmentioning
confidence: 99%
“…Aspirin-induced COX inhibition enhances the generation of anti-inflammatory lipoxins, such as 15-epi-lipoxin, which has protective effects on post-ischemic hyperperfusion and lung injury (46,75). P2Y 12 is also found on other cell types (76), and exerts non-platelet mediated pro-and anti-inflammatory ef-fects on leukocytes (77,78) and mediates leukocyte migration in transplant arteriosclerosis independently of platelet P2Y 12 (79). The effect of aspirin and P2Y 12 inhibitors on leukocyte functions further seems to depend on the pathological condition of the patient or on the disease models as effects observed in healthy volunteers are not always reflected by patient cohorts (80).…”
Section: Effects Of Aspirin and P2y 12 Antagonists On Platelet-leukocmentioning
confidence: 99%
“…Forty-eight hours after the last dose, animals were euthanized, plasma was separated, and liver tissue was extracted as described above. Blood cell counts were determined using the Hemavet automatic counter, following the previously established protocol ( 62 , 63 ). Liver samples were rapidly frozen and embedded in optimal cutting temperature compound.…”
Section: Methodsmentioning
confidence: 99%
“…It is also noted that the majority of the patients were women [ 120 ]. In contrast with all the inflammation models previously reported, our group showed that, during erosive arthritis induced by peptidoglycan polysaccharide, the severity of the inflammation in the joints was augmented when animals were pre-treated with clopidogrel [ 15 ] or prasugrel [ 121 ]. This discrepancy between studies suggests that more investigations need to be carried out to understand how P2Y 12 antagonism can alter RA and to determine whether P2Y 12 antagonist exerts beneficial effects on this inflammatory condition.…”
Section: P2y 12 Activation In the Immune System Du...mentioning
confidence: 95%